2016
DOI: 10.1094/phyto-07-15-0180-r
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities in Globodera pallida Females Raised in Potato Monoculture Soil

Abstract: Globodera spp. are under strict quarantine in many countries. Suppressiveness to cyst nematodes can evolve under monoculture of susceptible hosts. Females developing in potato monoculture soil infested with G. pallida populations Chavornay or Delmsen were examined for inherent microbial communities. In the greenhouse, nonheated and heat-treated (134°C for 10 min) portions of this soil were placed in root observation chambers, planted with Solanum tuberosum 'Selma', and inoculated with G. pallida Pa3 Chavornay.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
0
16
0
1
Order By: Relevance
“…The decline of PPN populations in field soils was first reported in 1962 by Collingwood for the cyst nematode Heterodera avenae in the United Kingdom under intensive cropping of cereal hosts (Collingwood, 1962;Kerry, 1982). Since then, suppressive soils have been reported for several nematode species including H. avenae in the United Kingdom (Gair et al, 1969;Williams, 1969;Kerry, 1975), Heterodera schachtii in Netherlands, United Kingdom, and United States (Heijbroek, 1983;Crump and Kerry, 1987;Westphal and Becker, 1999), Globodera rostochiensis in Germany (Roessner, 1987), Globodera pallida in the United Kingdom and Germany (Crump and Flynn, 1995;Eberlein et al, 2016), Heterodera glycines in the United States and China (Chen et al, 1996b;Sun and Liu, 2000;Hamid et al, 2017;Hussain et al, 2018), the false root-knot nematode Nacobbus aberrans in Mexico (Zuckerman et al, 1989), root-knot nematodes Meloidogyne spp. in Mexico, United States, Spain, and Germany (Bird and Brisbane, 1988;Zuckerman et al, 1989;Chen et al, 1994b;Pyrowolakis et al, 2002; FIGURE 1 | Microbial antagonists of plant-parasitic nematodes and mechanisms of their antagonism.…”
Section: History Of Nematode-suppressive Soilsmentioning
confidence: 99%
See 3 more Smart Citations
“…The decline of PPN populations in field soils was first reported in 1962 by Collingwood for the cyst nematode Heterodera avenae in the United Kingdom under intensive cropping of cereal hosts (Collingwood, 1962;Kerry, 1982). Since then, suppressive soils have been reported for several nematode species including H. avenae in the United Kingdom (Gair et al, 1969;Williams, 1969;Kerry, 1975), Heterodera schachtii in Netherlands, United Kingdom, and United States (Heijbroek, 1983;Crump and Kerry, 1987;Westphal and Becker, 1999), Globodera rostochiensis in Germany (Roessner, 1987), Globodera pallida in the United Kingdom and Germany (Crump and Flynn, 1995;Eberlein et al, 2016), Heterodera glycines in the United States and China (Chen et al, 1996b;Sun and Liu, 2000;Hamid et al, 2017;Hussain et al, 2018), the false root-knot nematode Nacobbus aberrans in Mexico (Zuckerman et al, 1989), root-knot nematodes Meloidogyne spp. in Mexico, United States, Spain, and Germany (Bird and Brisbane, 1988;Zuckerman et al, 1989;Chen et al, 1994b;Pyrowolakis et al, 2002; FIGURE 1 | Microbial antagonists of plant-parasitic nematodes and mechanisms of their antagonism.…”
Section: History Of Nematode-suppressive Soilsmentioning
confidence: 99%
“…It was suggested that the application of formalin inhibited the parasitic fungi Nematophthora gynophila and Pochonia chlamydosporia and thereby resulted in an increased population density of H. avenae (Kerry et al, 1980;Kerry, 1988). Later, several studies demonstrated the microbial involvement in soil suppressiveness by soil autoclaving or heating (Bird and Brisbane, 1988;Zuckerman et al, 1989;Kluepfel et al, 1993;Chen et al, 1996b;Weibelzahl-Fulton et al, 1996;Westphal and Becker, 1999;Sun and Liu, 2000;Bent et al, 2008;Adam et al, 2014b;Eberlein et al, 2016;Giné et al, 2016;Hamid et al, 2017;Bhuiyan et al, 2018), by the application of biocides (Kerry et al, 1980;Crump and Kerry, 1987;Westphal and Becker, 1999;Sun and Liu, 2000;Westphal and Becker, 2001;Pyrowolakis et al, 2002;Yin et al, 2003a,b;Bent et al, 2008;Song et al, 2017), and through soil transplantation (Mankau, 1975;Stirling and Kerry, 1983;Kluepfel et al, 1993;Westphal and Becker, 2000;Sun and Liu, 2000;Yin et al, 2003a,b;Chen, 2007;Bent et al, 2008). Notably, the soil suppressiveness was also observed to be transferred by egg-suspensions of the root-knot nematode Meloidogyne incognita (Orion et al, 2001) and cysts of the sugar beet cyst nematode H. schachtii (Westphal and Becker, 2001).…”
Section: History Of Nematode-suppressive Soilsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chaetomium globosum Kunze was isolated from the eggs of Heterodera glycines and this fungus was found to reduce hatching in laboratory conditions. In a culture independent study of soil suppressive to G. pallida , Microdochium bolleyi (Sprauge) along with several other fungi were reported .…”
Section: Introductionmentioning
confidence: 99%